Implementasi Metode Multi Objective Optimization by Ratio Analysis dalam Menentukan Lahan dengan Jumlah Pupuk Terbanyak - Ikhwan, Ali; Yuanda, Ary Santri; Shiddiq Siregar, Fahreza; Lesmana, Reza Kurnia (Jurnal Algoritma, 2024)
PTPN III (Persero) is a plantation company that has a strategic role in managing agricultural resources in Indonesia. With a main focus on the plantation sector, PTPN III manages various types of crops such as oil palm, rubber and tea, which are the country's main export commodities. However, to get the best quality, accumulation must be taken into account in order to increase agricultural yields. This research aims to optimize agricultural management at PTPN III through the implementation of a Decision Support System (SPK) which utilizes the Multi-Objective Optimization by Ratio Analysis (MOORA) method. Decision Support Systems (DSS) are very helpful in determining and making decisions that cannot be chosen randomly. This system is designed to provide recommendations based on evaluation criteria. The aim of this system is to determine the blocks or sections that require the most fertilizer without any effort and efficiency. It is hoped that the results of this system will provide assistance to PTPN III. Experimental results show that implementing SPK using the MOORA method can help PTPN III identify the most suitable land and determine the largest amount of fertilizer to increase agricultural yields and serve as reference data. This system not only increases the efficiency of fertilizer use but also supports environmental sustainability. It is hoped that the accuracy and reliability of the SPK can become the basis for smarter and more adaptive decision making in modern agricultural management. The final result aimed at is to obtain land that uses the most fertilizer based on the final results, namely Block LL32 AFD IX (A4) with a score of 0.3334 and is in first position.